Krisis Otonomi Media Lokal: Analisis Model Propaganda Herman-Chomsky pada Harian Victory News dalam Kontestasi Pemilihan Gubernur NTT 2018 - Merlina Maria Barbara Apul (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2022)
This work is intended to answer how the consequences of media ownership by local elites on the production and construction of discourses of dominant-marginal figures of candidate pairs in the news on the 2018 NTT Governor Election in the Local Newspaper Victory News edition of February – June 2018. With these research questions, this research adopts a critical political economy perspective, instrumental approaches, and critical discourse analysis. The findings show that the different access of the elite to the media is responsible for producing different access to the structure of news reports. This access generates the following five filters 1.) Victory News as an instrument for adding Viktor Laiskodat's hand; 2.) Advertising as a source of income; 3.) Elite as the main news source; 4.) Criticism as a means of disciplining the media and 5.) Pancasila as the ideology of the Republic of Indonesia as a media control mechanism. Meanwhile, from the text level, four main findings can be drawn, namely 1.) Victory News has a minimum critical attitude; 2.) Reliance on elites as news sources; 3.) How and why to become a marginal element in the news Victory News; and 4.) The dominant words of hyperbole when describing the figure of the candidate pair Victory-Joss.